Structural, Optical, and Electrical Characterization of β-Ga2O3 Thin Films Grown by Plasma-Assisted Molecular Beam Epitaxy Suitable for UV Sensing. (18th March 2018) - Arias, Abraham; Nedev, Nicola; Ghose, Susmita; Rojas-Ramirez, Juan Salvador; Mateos, David; Curiel Alvarez, Mario; Pérez, Oscar; Suárez, Mariel; Valdez-Salas, Benjamin; Droopad, Ravi
Abstract : β -Ga2 O3 thin films were grown on c-plane sapphire substrates by plasma-assisted molecular beam epitaxy. The films were grown using an elemental gallium source and oxygen supplied by an RF plasma source. Reflection high-energy electron diffraction (RHEED) was used to monitor the surface quality in real time. Both in situ RHEED and ex situ X-ray diffraction confirmed the formation of single crystal β -phase films with excellent crystallinity on c-plane sapphire. Spectroscopic ellipsometry was used to determine the film thicknesses, giving values in the 11.6–18.8 nm range and the refractive index dispersion curves. UV-Vis transmittance measurements revealed that strong absorption of β -Ga2 O3 starts at ∼270 nm. Top metal contacts were deposited by thermal evaporation for I-V characterization, which has been carried out in dark, as well as under visible and UV light illumination. The optical and electrical measurements showed that the grown thin films of β -Ga2 O3 are excellent candidates for deep-ultraviolet detection and sensing.